An equation is shown below:3(4x − 2) = 1

Which of the following correctly shows the steps to solve this equation?

Step 1: 12x − 2 = 1; Step 2: 12x = 3
Step 1: 12x − 6 = 1; Step 2: 12x = 7
Step 1: 7x + 1 = 1; Step 2: 7x = 0
Step 1: 7x − 5 = 1; Step 2: 7x = 6

Answers

Answer 1
Answer: 12x-6=1
12x=7
---------
Answer 2
Answer:

Answer:

1: 12x − 6 = 1

2: 12x = 7

Step-by-step explanation:


Related Questions

Latisha earns $5 an hour painting her neighbor's fence. Write an equation to represent the relationship between the two variables.
What is half of a quarter of 400?
I am confused on numbers 25 and 29, the instructions are at the top.
A stem-and-leaf plot uses pictures or symbols to represent information.TrueFalse
Tomas learned that the product of the polynomials (a + b)(a2 – ab + b2) was a special pattern that would result in a sum of cubes, a3 + b3. His teacher put four products on the board and asked the class to identify which product would result in a sum of cubes if a = 2x and b = 1.Which product should Tomas choose? A) (2x + 1)(2x2 + 2x – 1) B) (2x + 1)(4x3 + 2x – 1) C) (2x + 1)(4x2 – 2x + 1) D) (2x + 1)(2x2 – 2x + 1)

PLSSS HELPPPP I WILLL GIVE YOU BRAINLIEST!!!!!!A sequence is shown.
3, 9, 13, 33, 51, ...
Which of the following functions can be used to find the nth tern of this sequence?
a.f(n)=n^2+2

b.f(n)=2n^2+1

c.f(n)=2n+1

d.f(n)=3n^2

Answers

Answer:

b. f(n) = 2n^2 + 1

Step-by-step explanation:

Thanks for explaining the nth thing to me. It all makes sense now :'D

I'll be honest I think you're at least a grade level above me in math.

It's b. because

f(n) = 2(1)^2 + 1

        2(1) + 1

        2 + 1 = 3 (first term)

f(n) = 2(2)^2 + 1

        2(4) + 1

        8 + 1 = 9 (second term)  ...and so on. :)

What the sum of the first seven terms 4,12,36,108

Answers

4,12,36,108,324,972,2916.

The pattern is each number is getting 3x bigger.

If you add all of the numbers, you will get 4372.

If h(x) = −4x − 10, find h(−5).

−30
1.25
10
−1

Answers

The value of function h (-5) will be;

⇒ h (-5) = 10

What is substitution method?

To find the value of any one of the variables from one equation in terms of the other variable is called the substitution method.

Given that;

The function is,

⇒ h (x) = - 4x - 10

Now,

Here, The function is,

⇒ h (x) = - 4x - 10

So, To find the value of h (-5) as;

Substitute x = - 5 in above equation as;

⇒ h (x) = - 4x - 10

⇒ h (-5) = - 4 × -5 - 10

⇒ h (-5) = 20 - 10

⇒ h (-5) = 10

Thus, The value of function h (-5) will be;

⇒ h (-5) = 10

Learn more about the substitution method visit:

brainly.com/question/26094713

#SPJ2

h(x)=-4x-10\n\nh(-5)\to x=-5\n\nsubtitute\ the\ value\ of x=-5\ to\ the\ formula:\n\nh(-5)=-4(-5)-10=20-10=\boxed{10}

Find the quotient

4 / 9/10

Answers

Answer:

4 × 10/9 = 40/9 is the solution

8.7w-3=5.5w+3.4
Please solve ​

Answers

Answer:

w=2

Step-by-step explanation:

8.7w-3=5.5w+3.4

-5.5w   -5.5w

3.2w-3= 3.4

       +3    3

3.2w= 6.4

w=2

9d + 2 = 56
The solution is d =

Answers

Answer:6

Step-by-step explanation:9x6=54

54+2=56

Answer:the solution is d=6

Step-by-step explanation:9*6+2=56